The Intergenerational Dialogue of the Family Crecente in "Os libros arden mal" by Manuel Rivas - Lammers, Anna (Madrygal. Revista de Estudios Gallegos, 2015)
This article analyses the dialogue of the Crecente family in the novel Oslibrosarden mal (2006) of the Galician writer Manuel Rivas. From the theoretical concepts in collective memory, cultural memory and collective trauma, developed in Social and Cultural Sciences by Halbwachs (1925), Assmann (1992) and Kühner (2008), the analysis focuses on the family’s traumatic memories of the Civil War and Franco’s regime and how they were transmitted.
Keywords: Galician literature; Manuel Rivas; Spanish Civil War; historical memory; intergenerational transmission